Efektivitas Bioremedian dan Konsorsia Mikroba Penyubur terhadap Produksi dan Kandungan Timbal Gabah di Karanganyar - Muslikhatun Mutmainnah; Edi Purwanto; Bambang Sukmadi; Supriyadi Supriyadi (Agrosains : Jurnal Penelitian Agronomi, 2014)
Food need in Indonesia always increases while its production tends to decrease. One of factors causing it is contaminants in agricultural environment including lead (Pb). This research aimed to study the effectiveness of bioremediation and microbial consortia fertilizers in increasing rice production and decreasing lead contamination in grain. The research started in August 2013 to February 2014 in village Waru and Kebak, Kebakkramat, Karanganyar, using Nested Factorial Treatment Design and Complete Randomized Block Design with two factors those are bioremediation variety and combination microbial fertilizers with chemical fertilizers. Statistical analysis used F-test, Kruskal Wallis,Tukey 5%, Mood Median, correlation test and regression. Research result showed best production was achieved at V2P1 (Pepe + Azolla 0,183 ton ha-1, microbial fertilizer 0,56 ton ha-1 and chemical fertilizers 50% of farmer standard), that is highest result is achieved at total number of tillers (35,64), number of productive tillers (25,72), Dry Grain (11 ton ha-1) and Dry Milled Grain (8,7 ton ha-1). Azolla microphylla, microbial fertilizer and chemical fertilizers 50% of farmer standard treat was effective to reduce heavy metal residues because lead residues were not found on the grain (0 ppm).